A Study of the Current Situation and Problems of Early Childhood Chinese Language Teaching - Kittachotworakul, Pongsathorn (Interdisciplinary Academic and Research Journal, 2023)
Many early childhood schools in Thailand, either government or private schools, use the content of the early childhood education curriculum as a guide for creating the school curriculum. In this area of policy, policymakers promote the teaching of a second language (Chinese) at all levels. In Thailand, Chinese language extracurricular activities have begun in early childhood and many researches have appeared at the same time. This quantitative research article aimed to study the current situation and problems of early childhood Chinese language teaching. The research sample consisted of 134 Thai early-childhood Chinese teachers selected by simple random sampling. The research instruments were questionnaires and descriptive statistics were used for data analysis. The study found as follows: 1) Current situation of teaching Chinese in Thai kindergartens: most of the respondents indicate that Chinese in kindergartens was 1 period per week in instructional management, the average instruction was around 36-45 minutes, and Thai was used as the main language in instruction. And most of the respondents agreed on 6 issues: dissemination of teaching activities, systematic development of Chinese curriculum in kindergartens, promoting Chinese writing, creating a connection to another level, promoting the use of textbooks, and the use of the immersion language teaching model. 2) Problems related to Chinese language instruction at the early childhood level: there were 6 issues surveyed-- important problems affecting instruction, evaluation, policy and structure, content scope, media, and teaching equipment and suggestions.